2012
DOI: 10.4103/0253-7613.96298
|View full text |Cite
|
Sign up to set email alerts
|

Alcea rosea root extract as a preventive and curative agent in ethylene glycol-induced urolithiasis in rats

Abstract: Introduction:Alcea rosea L. is used in Asian folk medicine as a remedy for a wide range of ailments. The aim of the present study was to investigate the effect of hydroalcoholic extract of Alcea rosea roots on ethylene glycol-induced kidney calculi in rats.Materials and Methods:Male Wistar rats were randomly divided into control, ethylene glycol (EG), curative and preventive groups. Control group received tap drinking water for 28 days. Ethylene glycol (EG), curative and preventive groups received 1% ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…[ 91 ], Tribulus terrestris L. [ 92 ], Acalypha indica L. [ 93 ], Aerva lanata (L.) Juss. [ 94 ], Ageratum conyzoides (L.) L. [ 11 ], Alcea rosea L. [ 95 ], Asparagus racemosus Willd. [ 96 ], Bombax ceiba L. [ 97 ], Carthamus tinctorius L. [ 98 ], Cynodon dactylon (L.) Pers.…”
Section: Medicinal Plants and Phytoconstituents As Dietary Supplemmentioning
confidence: 99%
“…[ 91 ], Tribulus terrestris L. [ 92 ], Acalypha indica L. [ 93 ], Aerva lanata (L.) Juss. [ 94 ], Ageratum conyzoides (L.) L. [ 11 ], Alcea rosea L. [ 95 ], Asparagus racemosus Willd. [ 96 ], Bombax ceiba L. [ 97 ], Carthamus tinctorius L. [ 98 ], Cynodon dactylon (L.) Pers.…”
Section: Medicinal Plants and Phytoconstituents As Dietary Supplemmentioning
confidence: 99%
“… 2016 ), antiurolithiatic, diuretic anti-inflammatory (Ahmadi et al. 2012 ), antibacterial (Lim 2014 ), hepatoprotective (Hussain et al. 2014 ), analgesic and cytotoxic activities (Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…showed that hydroalcoholic extract of Alcearosea had both preventive and curative effects on the formation of CaOx calculi apparently due to its diuretic and anti-inflammatory activities, presence of mucilaginous polysaccharides, and lowering of urinary concentrations of stone-forming constituents. [ 23 ] Low volume of urine is one the risk factors of nephrolithiasis due to hypersaturation of all solutes. [ 23 24 ] It has been reported that A. millefolium has diuretic effects and increases diuresis by 25% from initial volume without changing of urine pH in the patients with calcium type of urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Low volume of urine is one the risk factors of nephrolithiasis due to hypersaturation of all solutes. [ 23 24 ] It has been reported that A. millefolium has diuretic effects and increases diuresis by 25% from initial volume without changing of urine pH in the patients with calcium type of urolithiasis. [ 24 ] Therefore, the diuretic effect of A. millefolium may be another possible mechanism involved in prevention of new calculi formation and dissolution of preformed stones.…”
Section: Discussionmentioning
confidence: 99%